2013
DOI: 10.1177/2150131913495243
|View full text |Cite
|
Sign up to set email alerts
|

Using Electronic Medical Record Data to Characterize the Level of Medication Use by Age-Groups in a Network of Primary Care Clinics

Abstract: Electronic medical record data may be an important tool for providing more comprehensive information regarding medication usage. Medication usage assessed by electronic medical records, even among the youngest cohort, appears to be greater than other sources of medication usage indicate. Higher levels of medication use were associated with a number of factors, including gender, body mass index, number of patient encounters, and comorbid conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Some 52% of the participants had more than 4 prescribed drugs which was higher than in other studies reporting a prevalence based on health surveys of between 26 and 40% [54]. It was, however, closer to those authors employing electronic healthcare records [55] who observed over 50%. In our study, polypharmacy predicted NH entry, a fact that might be related to multimorbidity in addition to adverse drug reactions/ interactions, and greater risk of falls, and negative health outcomes [56].…”
Section: Polypharmacysupporting
confidence: 40%
“…Some 52% of the participants had more than 4 prescribed drugs which was higher than in other studies reporting a prevalence based on health surveys of between 26 and 40% [54]. It was, however, closer to those authors employing electronic healthcare records [55] who observed over 50%. In our study, polypharmacy predicted NH entry, a fact that might be related to multimorbidity in addition to adverse drug reactions/ interactions, and greater risk of falls, and negative health outcomes [56].…”
Section: Polypharmacysupporting
confidence: 40%
“…Some 52% of the participants had more than 4 prescribed drugs which was higher than in other studies reporting a prevalence based on health surveys of between 26 and 40% [55]. It was, however, closer to those authors employing electronic healthcare records [56] who observed over 50%. In our study, polypharmacy predicted NH entry, a fact that might be related to multimorbidity in addition to adverse drug reactions/interactions, and greater risk of falls, and negative health outcomes [57].…”
Section: Polypharmacysupporting
confidence: 40%
“…However, today’s state-of-the-art NLP programs are far from 100 % accurate—for example, their accuracy is poor because of the highly abbreviation-filled text of clinical notes [ 7 ]. Further, NLP information-extraction programs cannot be reused across all research applications [ 8 ]: to achieve high sensitivity and specificity, they must typically be tailored to specific problems, e.g., chronic pain [ 9 ], incontinence [ 10 ], and asthma [ 11 ].…”
Section: Discussionmentioning
confidence: 99%